2021
DOI: 10.1016/j.frl.2020.101687
|View full text |Cite
|
Sign up to set email alerts
|

#MeToo meets the mutual fund industry: productivity effects of sexual harassment

Abstract: Sexual harassment, a widespread problem in the workplace, arguably keeps female employees from optimally employing their human capital. We show that removing or diminishing this friction improves productivity. Specifically, using the male-dominated fund industry as our testing ground, we show that productivity of female mutual fund managers significantly increased after the Harvey Weinstein scandal and the onset of the #MeToo movement. Evidence from lawsuits and organizational changes at several fund companies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…It is our understanding that these types of aggregated data (which do not include firm-specific outputs) cannot distinguish between tastes and productivity. In fact the distinction is blurred given that discrimination in the shape of, for instance, workplace sexual harassment causes gender productivity differences (Folke and Rickne 2020;Cici et al 2021).…”
Section: Related Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…It is our understanding that these types of aggregated data (which do not include firm-specific outputs) cannot distinguish between tastes and productivity. In fact the distinction is blurred given that discrimination in the shape of, for instance, workplace sexual harassment causes gender productivity differences (Folke and Rickne 2020;Cici et al 2021).…”
Section: Related Literaturementioning
confidence: 99%
“…Thus the α 4,skl,occ,t share parameter we estimate could be capturing changes in discrimination over time or changes in real productivity. Empirically, real productivity and discrimination are also entangled: recent research literature has found that gender-based discrimination (harassment) has real productivity impacts (Folke and Rickne 2020;Cici et al 2021), see the related discussion in Section 1.1.…”
Section: Demand Sidementioning
confidence: 99%
“…Mutual fund managers that integrate gender equality‐related criteria in their investment processes could achieve different financial performance depending on the economic sector in which they invest. Previous literature examining the effect that the level of gender equality achieved by firms in which mutual funds invest has on the financial performance of their portfolios is scarce (Cici et al, 2021; Rao et al, 2020). To fill this gap, this study examines the effect of gender equality criteria on the financial performance of SDG‐related thematic mutual funds in the United States.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…This study contributes to the previous literature in different ways. First, it considers several dimensions of gender equality, as described in the previous paragraph, while other studies have examined the effects of sexual harassment (Cici et al, 2021), gender diversity in the workforce (Peillex et al, 2021), and gender diversity on boards (Chapple & Humphrey, 2014). Second, it groups fund portfolios by SDG‐related sectors as well as considering fund portfolios that are diversified across sectors, thus enabling us to identify the contrasting relationships between fund financial performance and gender equity scores depending on the sector.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation